Briefing: An integrated approach to asset management system IT selection and implementation. Issue 3 (26th May 2017) - Simpson, David; Harris, Neil
Abstract : Information technology (IT) systems are recognised as key tools for supporting organisations that need to make asset management decisions based on increasing volumes of data and expanding business objectives. The authors of this paper reflect on their experiences from reviewing an existing asset management IT system and planning the next phase of IT system development in order to support the attainment of key business objectives on a 30-year highway Design–Build–Finance–Operate project. This paper focuses on general insights derived from the journey through this complex process and attempts to simplify and share lessons, which it is hoped are applicable to wider fields of asset management.